Self-protecting PVDF-PDA-TiO₂ membranes towards highly efficient and prolonged dye wastewater treatment by photocatalytic membranes - Le, Thi My Hanh (2023)
The photocatalytic membranes have been reported to treat textile dye effluents; however, it is challenging to maintain their long-term functionality due to the poor binding stability of nanoparticles on the membrane surface and the low stability of the membrane to UV radiation. To address this, PVDF photocatalytic hollow fiber membranes were prepared by coating with polydopamine (PDA) for 1–4 h, then with titanium dioxide nanoparticles (TiO2) in the current study. SEM and EDX results showed that TiO2 adhered firmly to the PDA-pretreated membrane after ultrasonic treatment. The PDA layer protected the membranes from UV irradiation. The PVDF-TiO2 membrane without PDA pretreatment was destroyed after 24 h of UV irradiation, while after 9 days of continuous irradiation, the membranes treated with PDA for 2 h remained unchanged. Compared with the original membrane, applying PVDF membranes coated with PDA for 2 h and TiO2 for 1 h increased the Reactive Red 239 rejection and flux recovery rates by 13% and 40%, respectively, achieving 60% COD removal. The permeate flux and dye rejection rate were stable after 5 cycles (20 h of operation). This study demonstrates that the obtained membranes can perform prolonged membrane filtration with high-performance durability for dye wastewater treatment.